Methods for assessing selected disorders of the autonomic nervous system in neurodegenerative diseases - Karolina Kubiak; Klaudia Kwiatkowska; Martyna Lamtych; Nataliia Badiuk (Kazimierz Wielki University, 2018)
Neurodegenerative diseases belong to the group of progressive disease entities leading to pathological changes in nerve cells. Loss of nerve cells causes numerous motor and non-motor disorders, which include autonomic nervous system (AUN) disorders. The aim of the study is to review the available literature on the most frequently occurring disorders of the autonomic nervous system occurring in neurodegenerative diseases and methods of their diagnosis. For this purpose, databases such as MedLine, PubMed, Cochrane Library and Polish Medical Bibliography were searched. Articles in Polish and English were selected. The paper presents the methods most commonly used to assess the autonomic nervous system, cardiovascular disorders. Accounted for methods that, thanks to their ease of implementation, have found wide clinical application. Non-invasive methods include, among others: analysis of heart rate variability, 24-hour blood pressure monitoring, tilt test and deep slow breathing test. In addition to the above-mentioned studies and tests, the literature also includes questionnaires for assessing dysautonomy. The most commonly used is the Lowa Autonomous Symptom Questionnaire. Studies published so far confirm the need to use AUN assessment in neurodegenerative diseases. Diagnosis and treatment of nervous system dysautonomics is important from the point of view of a holistic therapeutic approach.